2021
DOI: 10.1186/s12877-021-02160-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of quetiapine for delirium prevention in hospitalized older medical patients: a randomized double-blind controlled trial

Abstract: Background Delirium is a common disorder among hospitalized older patients and results in increased morbidity and mortality. The prevention of delirium is still challenging in older patient care. The role of antipsychotics in delirium prevention has been limited. Therefore, we conducted a trial to investigate the efficacy of quetiapine use to prevent delirium in hospitalized older medical patients. Methods This study was a randomized double-blind c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…In another trial comparing quetiapine (n = 24) to haloperidol (n = 28), one patient with malignancy and sepsis died in each study arm [18]. Furthermore, quetiapine failed to improve the length of hospital or ICU stay, or to reduce mortality, when it was used either as a delirium prevention agent in older or high-risk patients, or as a treatment agent for hypoactive delirium [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In another trial comparing quetiapine (n = 24) to haloperidol (n = 28), one patient with malignancy and sepsis died in each study arm [18]. Furthermore, quetiapine failed to improve the length of hospital or ICU stay, or to reduce mortality, when it was used either as a delirium prevention agent in older or high-risk patients, or as a treatment agent for hypoactive delirium [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have investigated its effects on the incidence of delirium in critically ill patients, and the results suggest that dexmedetomidine may effectively reduce the incidence of delirium in this population [29,30]. Saran et al reported that quetiapine prophylactic therapy does not reduce the incidence of delirium in hospitalized elderly patients [31]. However, treatment with antipsychotic drugs and antidepressants can alleviate delirium symptoms in some hospitalized patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among olanzapine, risperidone, haloperidol, and quetiapine, quetiapine has been the most extensively studied. A dose of 12.5 mg each evening was found to be insufficient in reducing the risk of delirium (14). The authors suggest that a higher dose in a more selective subgroup might be beneficial for quetiapine.…”
Section: Sedation Protocolmentioning
confidence: 95%
“…COVID-19 infection does not appear to present significant challenges in terms of sedation or allowing physical therapy in VV-ECMO patients. Among opioids, melatonin, benzodiazepines, and antidepressants, only antipsychotics have been shown to be effective in preventing delirium after discontinuing dexmedetomidine (14). Haloperidol, at a dose of 1 mg, is also utilized to prevent nausea in postoperative general surgery patients and to prevent delirium (as reported in the recovery room anesthesia order set by the University of California).…”
Section: Sedation Protocolmentioning
confidence: 99%